Analysis of Persuasive Messages on TikTok Influencer 'Relationship' Content: Its Impact on Audience Behavior - Nasyifa Mawar Septiyani; Rahmanto, Andre; Anshori, Mahfud (Al-Hiwar Jurnal Ilmu dan Teknik Dakwah, 2024)
This study analyzes the use of persuasive communication in TikTok content @nmaliccaa, which focuses on relationship tips. The study aims to find out how persuasive communication is in Relationship content on the TikTok account @nmaliccaa. This research uses Carl Hovland's persuasive communication theory to explore the application of persuasive communication techniques by TikTok creator @nmaliccaa in her Relationship content. The method applied in this study is descriptive qualitative and content analysis; we observe specific video content that discusses Relationships. The results of the analysis show that @nmaliccaa effectively uses persuasive communication techniques from Onong Uchana Effendy, such as association, integrity, rewards, order, and red-herring. The use of relaxed, personal, and relevant language to the audience's experience, as well as the delivery of solutions to common problems in relationships, are the keys to @nmaliccaa's success in influencing her audience. @nmaliccaa's content on Relationships has succeeded in attracting a wide audience and triggering behavioural change. This study confirms TikTok's potential as an effective platform for spreading persuasive messages and inspiring behavioural change.